2013
DOI: 10.1113/jphysiol.2013.263319
|View full text |Cite
|
Sign up to set email alerts
|

Daily variation in the electrophysiological activity of mouse medial habenula neurones

Abstract: Intrinsic daily or circadian rhythms arise through the outputs of the master circadian clock in the brain's suprachiasmatic nuclei (SCN) as well as circadian oscillators in other brain sites and peripheral tissues. SCN neurones contain an intracellular molecular clock that drives these neurones to exhibit pronounced day–night differences in their electrical properties. The epithalamic medial habenula (MHb) expresses clock genes, but little is known about the bioelectric properties of mouse MHb neurones and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 61 publications
(147 reference statements)
2
53
0
Order By: Relevance
“…Based on the results, SCN neurons were classified as either (i) silent, (ii) spiking, (iii) having depolarized electrical states with low-amplitude membrane oscillations or (iv) exhibiting depolarization block, in which spiking could be reinstated by injecting hyperpolarizing current (Supplementary Fig. 2) as reported in other brain areas2021 as well as in the SCN16. In the remaining spontaneously spiking neurons, APs were separated (or generated) by smooth depolarizing ramps to threshold (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the results, SCN neurons were classified as either (i) silent, (ii) spiking, (iii) having depolarized electrical states with low-amplitude membrane oscillations or (iv) exhibiting depolarization block, in which spiking could be reinstated by injecting hyperpolarizing current (Supplementary Fig. 2) as reported in other brain areas2021 as well as in the SCN16. In the remaining spontaneously spiking neurons, APs were separated (or generated) by smooth depolarizing ramps to threshold (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These findings support the view that in vertebrates, orexin signaling plays pivotal roles in the timing of transitions in brain and behavioral states (Mochizuki et al, 2004;Elbaz et al, 2012). Since the neural circadian system is extensive (Sakhi et al, 2013) and because orexin neurons innervate many components of this circadian timing circuitry (Peyron et al, 1998), it is important to understand how orexin signaling integrates with circadian time cues to influence neuronal activity in these areas. A key implication is that the mechanisms of orexin's actions in the SCN switch from predominantly GABA-mediated presynaptic actions during the day to robust direct postsynaptic effects at night.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported that temporal variations in the habenula complex was limited to the LHb1320 however, recently, the medial habenular neurons are also shown to exhibit daily variations similar to our observations. In this study, daily variations were no longer observed in clock gene deficient animals, suggesting that the temporal dynamics could be directly regulated by the expression of clock-related genes34. Thus, the excitability of the entire habenula complex is likely under the circadian control.…”
Section: Discussionmentioning
confidence: 60%
“…More importantly, the variations include a significant shift in the dominance of highly active population of neurons and primarily rise from presynaptic efficacy of neurotransmitter release. This is of particular interest given that the LHb activity in animal models of depression were presynaptically but not postsynaptically potentiated and the high-frequency neurons are likely to make greater contribution to the observed abnormal potentiation in helpless rodent models34.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation